The importance of Open Science in Business Studies and Economics. An empirical study by the ZBW – Leibniz Information Centre for Economics - Doreen Siegfried; Guido Scherp; Stephanie Linek; Elisabeth Flieger (ZBW – Leibniz Information Centre for Economics, 2024)
This study examines Open Science practices among economic researchers at German universities and research institutions. A total of 314 scientists from different economic disciplines took part in an online survey to answer questions about their attitudes, applications, barriers, and incentives in relation to Open Science. The need for support in this area was also identified. The results show an increasing acceptance and implementation of Open Science methods, with significant differences between different types of institutions. The management of research data, the use of Open Access publications, and the integration of Open Data and codes into the publication process were identified as key aspects. The study provides a comprehensive insight into the current landscape and challenges of Open Science in economic research.
Keywords: 330; Open Science; Open Science practices; Open Access; Open Data; repoducibility; transparency; science